2011
DOI: 10.1186/1743-422x-8-155
|View full text |Cite
|
Sign up to set email alerts
|

Role of HCV Core gene of genotype 1a and 3a and host gene Cox-2 in HCV-induced pathogenesis

Abstract: BackgroundHepatitis C virus (HCV) Core protein is thought to trigger activation of multiple signaling pathways and play a significant role in the alteration of cellular gene expression responsible for HCV pathogenesis leading to hepatocellular carcinoma (HCC). However, the exact molecular mechanism of HCV genome specific pathogenesis remains unclear. We examined the in vitro effects of HCV Core protein of HCV genotype 3a and 1a on the cellular genes involved in oxidative stress and angiogenesis. We also studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
(61 reference statements)
1
30
0
Order By: Relevance
“…These data are consistent with earlier studies that reported the important role of Core and NS5A in stimulating the production of several key factors involved in fibrosis (TGF‐β) and angiogenesis (VEGF) through multiple signalling pathways, including PI3K, JNK/p38 and ERK . Also, other studies have described that the structural proteins E1 and E2 may be implicated in pathological regenerative angiogenesis …”
Section: Discussionsupporting
confidence: 93%
“…These data are consistent with earlier studies that reported the important role of Core and NS5A in stimulating the production of several key factors involved in fibrosis (TGF‐β) and angiogenesis (VEGF) through multiple signalling pathways, including PI3K, JNK/p38 and ERK . Also, other studies have described that the structural proteins E1 and E2 may be implicated in pathological regenerative angiogenesis …”
Section: Discussionsupporting
confidence: 93%
“…Seventh, development of many types of tumors including HCC depends on efficient angiogenesis [145,146]. It was revealed that HCV infection leads to up-regulation of cyclooxygenase 2 (COX-2), increased production of prostaglandin E2 (PGE2), and vascular endothelial growth factor (VEGF) [147,148]—a crucial regulator of angiogenesis and apoptosis prevention [149,150,151]. Interestingly, this was demonstrated using NS5A and core proteins which caused oxidative stress and up-regulation of ROS-sensitive NF-κB transcription factor [50,148].…”
Section: Oxidative Stress and Hcv-associated Diseasesmentioning
confidence: 99%
“…It was revealed that HCV infection leads to up-regulation of cyclooxygenase 2 (COX-2), increased production of prostaglandin E2 (PGE2), and vascular endothelial growth factor (VEGF) [147,148]—a crucial regulator of angiogenesis and apoptosis prevention [149,150,151]. Interestingly, this was demonstrated using NS5A and core proteins which caused oxidative stress and up-regulation of ROS-sensitive NF-κB transcription factor [50,148]. It is worth noting that PGE2 also contributes to tumor survival by other mechanisms [152], one of which could be activation of antiapoptotic PI3K/AKT signaling pathway [147].…”
Section: Oxidative Stress and Hcv-associated Diseasesmentioning
confidence: 99%
“…et al (19). DNA fragments encoding induced iNOS, COX-2 and VEGF were amplified using the primer pairs described by Jahan et al (32).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%